Helminth absence and invasion success of blackchin tilapia (Sarotherodon melanotheron) in Thailand - NANNAPHAT SUWANNARAT; Alexis Ribas; Jordi Miquel; Srisupaph Poonlaphdecha (Frontiers in Veterinary Science, 2025)
Introduction: in Thailand has raised concerns about its ecological and economic impacts. Methods: We surveyed 164 blackchin tilapia from six different locations in Chumphon Province, Thailand, including the sea, estuary, canal, and shrimp farms, examining them for helminths. Fishermen provided data on the first capture dates in the surveyed areas to determine how long the populations have been established. Results: No helminths were detected in any of the examined fish. The absence of parasites was consistent across all surveyed environments, suggesting a lack of parasitic burden in the population. Discussion: in Thailand, supporting the Enemy Release Hypothesis.
Keywords: Parasite Biology and Host Interactions; Fish Biology and Ecology Studies; Crustacean biology and ecology